The Challenges of Technology and Economic Catch-up in Emerging Economies - Lee, Jeong-Dong; Lee, Keun; meissner, dirk; Radosevic, Slavo; Vonortas, Nicholas (Oxford University Press, 2021)
This book synthesizes and interprets existing knowledge on technology upgrading failures as well as lessons from successes and failures in order to better understand the challenges of technology upgrading in emerging economies. The objective is to bring together in one volume diverse evidence regarding three major dimensions of technology upgrading: paths of technology upgrading, structural changes in the nature of technology upgrading, and the issues of technology transfer and technology upgrading. The knowledge of these three dimensions is being synthesized at the firm, sector, and macro levels across different countries and world macro-regions. Compared to the old and new challenges and uncertainties facing emerging economies, our understanding of the technology upgrading is sparse, unsystematic, and scattered. While our understanding of these issues from the 1980s and 1990s is relatively more systematized, the changes that took place during the globalization and proliferation of GVCs, the effects of the post-2008 events, and the effects of the current COVID-19 and geopolitical struggles on technology upgrading have not been explored and compared synthetically. Moreover, the recent growth slowdown in many emerging economies, often known as a middle-income trap, has reinforced the importance of understanding the technology upgrading challenges of catching-up economies. We believe that the time is ripe for "taking stock of the area" in order to systematize and evaluate the existing knowledge on processes of technology upgrading of emerging economies at the firm, sector, and international levels and to make further inroads in research on this issue. This volume aims to significantly contribute towards this end.